ZnO-nanostructure-based electrochemical sensor: Effect of nanostructure morphology on the sensing of heavy metal ions - Krasovska, Marina; Gerbreders, Vjaceslavs; Mihailova, Irena; Ogurcovs, Andrejs; Sledevskis, Eriks; Gerbreders, Andrejs; Sarajevs, Pavels (Beilstein Journal of Nanotechnology, 2018)
ZnO nanostructures are promising candidates for use in sensors, especially in electrochemical sensors and biosensors, due to their unique physical and chemical properties, as well as sensitivity and selectivity to several types of contamination, including heavy metal ions. In this work, using the hydrothermal method, nanostructures of ZnO were synthesized in four different morphologies: nanorods, nanoneedles, nanotubes and nanoplates. To determine the peculiarities of adsorption for each morphology, a series of electrochemical measurements were carried out using these nanostructured ZnO coatings on the working electrodes, using aqueous solutions of Pb(NO3)2 and Cd(NO3)2 as analytes with different concentrations. It was found that the sensitivity of the resulting electrochemical sensors depends on the morphology of the ZnO nanostructures: the best results were achieved in the case of porous nanostructures (nanotubes and nanoplates), whereas the lowest sensitivity corresponded to ZnO nanorods with a large diameter (i.e., low surface-to-volume ratio). The efficiency of sedimentation is also related to the electronegativity of adsorbate: it has been shown that all observed ZnO morphologies exhibited significantly higher sensitivity in detecting lead ions compared to cadmium ions.
Keywords: cadmium; electrochemical sensors; heavy metal ions; lead; one-dimensional nanostructures; ZnO

Molecular, Clinical and Environmental Toxicology - Tchounwou, P. B.; Yedjou, C. G.; Patlolla, A. K.; Sutton, D. J. (Heavy Metals Toxicity and the Environment, 2012)

(untitled) - Singh, S.; Barick, K. C.; Bahadur, D. (Nanomater. Nanotechnol., 2013)

(untitled) - Rasmussen, K. L.; Skytte, L.; Jensen, A. J.; Boldsen, J. L. (J. Archaeol. Sci.: Rep., 2015)

(untitled) - Pemmer, B.; Roschger, A.; Wastl, A.; Hofstaetter, J. G.; Wobrauschek, P.; Simon, R.; Thaler, H. W.; Roschger, P.; Klaushofer, K.; Streli, C. (Bone, 2013)

(untitled) - Rahman, M. M.; Khan, S. B.; Asiri, A. M.; Marwani, H. M.; Qusti, A. H. (Composites, Part B, 2013)

(untitled) - Venkatesham, V.; Madhu, G. M.; Satyanarayana, S. V.; Preetham, H. S. (Procedia Eng., 2013)

(untitled) - Khan, S. B.; Rahman, M. M.; Marwani, H. M.; Asiri, A. M.; Alamry, K. A. (Nanoscale Res. Lett., 2013)

(untitled) - Anjum, M.; Miandad, R.; Waqas, M.; Gehany, F.; Barakat, M. A. (Arabian J. Chem.)

Electrochemical Analysis of Proteins and Cells - Li, G.; Miao, P. (Theoretical Background of Electrochemical Analysis, 2013)

(untitled) - Wang, H. (Mod. Appl. Sci., 2010)

(untitled) - Wei, Z.; Yang, Y.; Wang, J.; Zhang, W.; Ren, Q. (J. Food Eng., 2018)

(untitled) - Ghodsi, J.; Rafati, A. A. (J. Electroanal. Chem., 2017)

(untitled) - Lu, Y.; Liang, X.; Niyungeko, C.; Zhou, J.; Xu, J.; Tian, G. (Talanta, 2018)

(untitled) - Bansod, B. K.; Kumar, T.; Thakur, R.; Rana, S.; Singh, I. (Biosens. Bioelectron., 2017)

(untitled) - Krasovska, M.; Gerbreders, V.; Paskevics, V.; Ogurcovs, A.; Mihailova, I. (Latv. J. Phys. Tech. Sci., 2015)

(untitled) - Krasovska, M.; Gerbreders, V.; Tamanis, E.; Gerbreders, S.; Bulanovs, A. (Latv. J. Phys. Tech. Sci., 2017)

(untitled) - Gerbreders, V.; Sarajevs, P.; Mihailova, I.; Tamanis, E. (Latv. J. Phys. Tech. Sci., 2015)

Proceedings Volume 9421, Eighth International Conference on Advanced Optical Materials and Devices (AOMD-8) - Mihailova, I.; Gerbreders, V.; Bulanovs, A.; Tamanis, E.; Sledevskis, E.; Ogurcovs, A.; Sarajevs, P. (Controlled growth of well-aligned ZnO nanorod arrays by hydrothermal method, Eighth International Conference on Advanced Optical Materials and Devices (AOMD-8), Riga, Latvia, 22.10.2014)

(untitled) - Xi, Y.; Song, J.; Xu, S.; Yang, R.; Gao, Z.; Hu, C.; Wang, Z. L. (J. Mater. Chem., 2009)

(untitled) - Chae, K.-W.; Zhang, Q.; Kim, J. S.; Jeong, Y.-H.; Cao, G. (Beilstein J. Nanotechnol., 2010)

(untitled) - Roza, L.; Rahman, M. Y. A.; Umar, A. A.; Salleh, M. M. (J. Alloys Compd., 2015)

(untitled) - Wang, H.; Li, G.; Jia, L.; Wang, G.; Tang, C. (J. Phys. Chem. C, 2008)

(untitled) - Altomare, A.; Camalli, M.; Cuocci, C.; Giacovazzo, C.; Moliterni, A.; Rizzi, R. (J. Appl. Crystallogr., 2009)

Hierarchical micro/nanostructured materials: fabrication, properties, and applications - Cai, W.; Duan, G.; Li, Y. (Structurally Enhanced Adsorption Performances for Environment, 2014)

(untitled) - Wang, X.; Cai, W.; Liu, S.; Wang, G.; Wu, Z.; Zhao, H. (Colloids Surf., A, 2013)

(untitled) - Zolfaghari, G.; Esmaili-Sari, A.; Anbia, M.; Younesi, H.; Ghasemian, M. B. (Int. J. Environ. Sci. Technol., 2013)

(untitled) - Wang, X.; Guo, Y.; Yang, L.; Han, M.; Zhao, J.; Cheng, X. (J. Environ. Anal. Toxicol., 2012)

(untitled) - Salariya, K.; Umar, A.; Kansal, S. K.; Mehta, S. K. (Sens. Actuators, B, 2017)

(untitled) - Ruslan, N. I.; Lim, D. C. K.; Alang Ahmad, S. A.; Abdul Aziz, S. F. N.; Supian, F. L.; Yusof, N. A. (J. Electroanal. Chem., 2017)

Spectroscopic Methods for Nanomaterials Characterization - Choudhary, Y. S.; Jothi, L.; Nageswaran, G. (Electrochemical Characterization, 2017)